MENTAL HEALTH AND ITS RELATIONSHIP TO SOME VARIABLES AMONG MOTHERS OF CHILDREN WITH AUTISM SPECTRUM DISORDER IN PALESTINE - Abu Al-Rob, Zainab Abdel Aziz Mohammed (An-Najah National University, 2025)
Background: The existence of a child with autism affects the mother as a result of her preoccupation with the needs of an autistic child who needs more care than an ordinary child. Mothers experience higher levels of stress and face more negative mental health outcomes in comparison with fathers, largely because they bear a greater share of caregiving responsibilities for their disabled child. Several factors play a significant role in influencing maternal mental health. Aim: The aim of this study is to investigate the relationship between mental health and some variables among mothers of children with autism disorder in Palestine Method: A cross-sectional study was conducted between February and September 2025 to examine the mental health status of mothers of children with autism spectrum disorder in Palestine and its association with selected socio-demographic and health-related variables. The study targeted a 398 convenience sample of mothers from rehabilitation centers in Jenin, Nablus, and Ramallah. Results: The results showed a high prevalence of psychological distress; all mothers expressed considerable distress with a mean of (49.09), and their GHQ scores were high on all subscales (The mean of Physical symptoms was (11.29), the mean of Anxiety and insomnia was (11.99), the mean of Social dysfunction was (13.30) and the mean of depression was (12.50). One-third reported having clinically significant PTSD symptoms with a the mean of (22.33), indicating a significant PTSD burden. The results also showed a significant and reciprocal correlation between GHQ and PTSD. Stated differently, a reciprocal link between PTSD and GHQ was discovered PTSD scores were significantly and positively associated with GHQ scores (p< .001, B = 0.183). GHQ scores were significantly and positively associated with PTSD scores. (p < .001, B = 0.741). The strongest predictors of GHQ were somatic symptoms (p < .001, B = 0.644) and anxiety/insomnia (p < .001, B = 0.926), although mothers' work and family health issues also increased risk. Husband's job was found to have a protective role, suggesting that shared responsibility and financial stability may buffer against PTSD. Recommendations: Based on the study results, the researcher recommended creating stress-reduction and counseling programs that target physical health issues, anxiety, and insomnia because these were the strongest indicators of PTSD. In addition, in order to lessen stigma and encourage early help-seeking, awareness efforts should be to raise professional and public knowledge of the psychological effects of raising children with ASD. The researcher also recommended encouraging stress reduction, good sleep hygiene, and relaxing techniques as part of daily family activities.
الصحة النفسية وعلاقتها ببعض المتغيرات لدى أمهات الأطفال ذوي اضطراب طيف التوحد في فلسطين